The role of mediator and moderator variables in suicidal ideation among adolescents in Gunungkidul, Yogyakarta, Indonesia - Haniek Farida; Sulistyo Budiarto; Siti Hafsah Budi Argiati; Ufuoma Patience Ejoke (Faculty of Psychology and Health - Universitas Islam Negeri Walisongo Semarang, 2025)
Adolescent mental health is influenced by resilience, which is defined as the ability to face challenges. Low resilience renders adolescents vulnerable to loneliness due to limited social support, which in turn heightens the risk of suicidal ideation. Social support can bolster resilience while mitigating the negative effects of loneliness; however, research positioning resilience as a mediator and social support as a moderator in this relationship remains limited, particularly among adolescents in high-risk areas such as Gunungkidul. This study aims to explore the role of resilience as a mediator and social support as a moderator in the relationship between loneliness and suicidal ideation. A quantitative cross-sectional correlational method was employed, together with a cluster random sampling technique. The sample comprised 420 students, consisting of 308 females and 112 males. The data collection technique used a social support scale, a resilience scale, and a suicidal ideation scale. The data were analyzed through a series of path analyses with the causal step method and MRA. Social support is shown to significantly moderate the direct effect of loneliness on resilience (p = .006 < .05), which indicates that social support increases. However, such support is unable to moderate the direct effect of resilience on suicidal ideation (p = .196 > .05), nor of loneliness on suicidal ideation (p = .338 > .05). The mediation effect test shows that loneliness does not have a significant effect on suicidal ideation when the resilience variable is controlled (p = .185 > .05). Regression model 2 in the mediation effect test indicates that only resilience has a significant effect on suicidal ideation (-.184 p < .05). The implications of the study include the understanding that suicidal ideation will be lower if accompanied by a decrease in loneliness and an increase in resilience and social support.